The Fingerprint based on Medical Information & Patient Retrieval - kalaiselvan, rufiney; Bahari, Azlina (Progress in Engineering Application and Technology, 2021)
The emergence of electronic health or eHealth system has revolutionized the healthcare industry to offer better healthcare services at a low and affordable cost. However, it still suffers from security and privacy issues in handling health information. The privacy and security issues in eHealth domain are mainly centered around user authentication, data integrity, data confidentiality, and patient privacy protection. Therefore, to cope with the above security problems biometrics technology has considerable opportunities by providing reliable and secure user authentication. However, due to the sensitive nature of health data, the most important challenge lies toward the development of an efficient security model that can guarantee data privacy and reliability, verifying that only authorized personnel can access their corresponding health data. In this paper, we present a comprehensive overview of biometrics applications in eHealth and propose a robust and efficient scheme for user verification using fingerprint biometrics in order to enhance privacy and security in eHealth information systems.